Social capital and household health-seeking behaviour for children in the context of urban neighbourhoods: The case of Khayelitsha in Western Cape, South Africa - Mwase, Isaac (Department of Public Health and Family Medicine, 2015)
Globally, almost 8 million children died in 2010 before reaching the age of 5 largely due to preventable diseases. Analysis of the distribution of child mortality indicators highlights huge differentials that still exist both between and within regions. Prompt seeking of appropriate healthcare by caregivers is critical for effective management of childhood illnesses and ultimately for mortality reduction. Studies have shown that households can draw on social capital, including trust and social networks, to improve health outcomes for children. Other studies have demonstrated that health outcomes may significantly differ across different neighbourhoods of the same community. Therefore, understanding social capital and healthcare-seeking behaviour in the context of neighbourhoods can help in the formulation of responsive health policies and strategies that promote child health and overall well-being for different populations. The objective of this study was to investigate social capital factors that are associated with healthcare-seeking behaviour of caregivers when their children become ill, using the case of neighbourhoods in Khayelitsha TownShip in the Western Cape Province of South Africa.